GREEN INNOVATION PRACTICE ON CORPORATE’S SUSTAINABLE GROWTH IN NON-FINANCIAL: THE MEDIATING EFFECT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING - Annisa Aulia Rahma Atmariani; Dian Agustia; Yani Permatasari; Gatra Kautsar Lusandi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This research explores the role of Environmental Management Accounting (EMA) as a mediator in the relationship between green innovation and sustainable growth. This research utilized the STATA 14 program to test hypotheses using the path analysis test and the Sobel test. The analysis was conducted on 2,716 observations from 539 non-financial corporates listed on the Indonesia Stock Exchange (IDX) between 2013 and 2020. The path analysis findings indicate that (1) green innovation positively influences EMA; (2) green innovation positively affects sustainable growth; (3) EMA does not have a significant impact on sustainable growth; and (4) EMA does not operate as a mediator between green innovation and sustainable growth. Additionally, the present research conducted a rigorous robustness test, which yielded results that aligned with those obtained from the path analysis test. Incorporating environmentally focused innovation into company plans provides substantial benefits for achieving sustainable growth, including cost reduction, improved competitive advantage, compliance with regulations, and exploring new market opportunities.